DAMPAK USER EDUCATION TERHADAP PEMANFAATAN SUMBER DAYA PERPUSTAKAAN UIN IMAM BONJOL PADANG - Lailatur Rahmi (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2022)
This research is motivated by the function of the university library as a very vital element in meeting the information needs of the academic community in carrying out the tridharma of higher education and none of these roles can be realized without an effective User Education program because this program aims to create awareness about how to make effective use of library services and resources. The purpose of this study was to describe the effectiveness of User Education activities on library use by students of the Faculty of Adab and Humanities UIN Imam Bonjol Padang. The research method is descriptive quantitative with a questionnaire as a primary data collection tool. The population of this research is all students of the Faculty of Adab and Humanities UIN Imam Bonjol Padang 2021-2022. Research questions were answer and analysis was performed using the mean scores. Research findings reveal that students of the Faculty of Adab and Humanities have various levels of understanding of the concept of User Education. The study also found that the User Education program positively influenced student use of the library and helped meet their academic information needs. The results of the study also found several problems that hindered User Activities effectively such as excess participants, lack of infrastructure, less innovative human resources, shortage of teaching materials, limited time allocated for activities, less conducive supporte and inadequate space. This study concludes that with a central place in student education, and to make user education programs indispensable, adequate resources should be provided to ensure that the ideal goals of the program are realized.